2022
DOI: 10.3389/fmicb.2022.1023971
|View full text |Cite
|
Sign up to set email alerts
|

Differential assembly of root-associated bacterial and fungal communities of a dual transgenic insect-resistant maize line at different host niches and different growth stages

Abstract: Transgenic technology has been widely applied to crop development, with genetically modified (GM) maize being the world’s second-largest GM crop. Despite the fact that rhizosphere bacterial and fungal populations are critical regulators of plant performance, few studies have evaluated the influence of GM maize on these communities. Plant materials used in this study included the control maize line B73 and the mcry1Ab and mcry2Ab dual transgenic insect-resistant maize line 2A-7. The plants and soils samples wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The analysis of functional genes in root-associated microbial communities was conducted by using the software PICRUSt and the Fungi Functional Guild (FUNGuild). All these analyses were performed on the platform I-Sanger ( https://cloud.majorbio.com ) as described previously ( 36 , 77 ).…”
Section: Methodsmentioning
confidence: 99%
“…The analysis of functional genes in root-associated microbial communities was conducted by using the software PICRUSt and the Fungi Functional Guild (FUNGuild). All these analyses were performed on the platform I-Sanger ( https://cloud.majorbio.com ) as described previously ( 36 , 77 ).…”
Section: Methodsmentioning
confidence: 99%
“…Turner et al [33] found that the structures of bacterial and fungal communities in the rhizosphere differ between pea and cereal crops. In addition, beneficial bacteria such as Actinobacteria and Rhizobia were found in the soil at the early stage of maize development, while at the late stage of development, the soil may be enriched with saprophytic fungi [34]. Moreover, perennial grassland legumes (e.g., alfalfa or clover) are usually associated with soil microorganisms involved in symbiotic and non-symbiotic N fixation and mycorrhizal associations [35].…”
Section: Introductionmentioning
confidence: 99%